Report from Libraries in the Digital Age (LIDA), June 13–17, 2016, Zadar, Croatia. Issue 4 (1st October 2016) - Moulaison Sandy, Heather
ABSTRACT: Libraries in the Digital Age (LIDA) 2016 takes place every 2 years, and was held this year at the University of Zadar, in Zadar, Croatia, from June 13–17, 2016. Each LIDA, two themes are chosen in advance. This year, the themes were "Digital Curation and Preservation: Current Trends and Research" and "Use Studies, Education, and Training for Digital Library Collections." A presentation of each theme by university professors and subsequent keynotes relevant to each theme by two world-renowned experts provided context and ensured a shared perspective among LIDA attendees. Conference-goers were presented a balanced approach to theoretical and practical questions in a number of areas of digital libraries, including the presentation of research on information seeking practices among special communities, data mining projects, the exploration of platforms and experiences, and digitization. Additionally, a number of the contributed papers, panels, demonstrations, and workshops spanned the two themes, making for not only an informative conference, but also a particularly rich and coherent experience for attendees. Opportunities for junior researchers were numerous, with the conference priding itself on the mentorship opportunities available. In 2018, you might find yourself tempted to see what LIDA is all about; if you do, you will no doubt find yourself in a breath-taking venue along the Croatian coast surrounded by engaged, supportive, and collaborative researchers and professionals from around the world – in my opinion, you won't regret it.